A comparison between Objective and subjective tests (Journal of the College of Languages (JCL), 2014)
This paper aims at presenting a comparison between objective and subjective tests . This paper attemptsto shed light on these two aspects of tests and make do a compression by using suitable techniques for objective and subjective tests . The paper compares between the two techniques used by the objective and subjective tests respectively, the time and efforts required by each type, the extent to which each type can be reliable, and the skills each type is suitable to measure. The paper shows that objective tests, on the contrary of the subjective ones, encourages guess> Objective tests are used to test specific areas of language; subjective tests give an overall evaluation of the student's mastery of language. The research investigates, in brief, the multiple- choice item being one of the widely used type of items in the objective tests: "answer these questions" being one of the widely used type of items in the subjective tests.The paper ends with the most important conclusions as a result of the research.